HETEROCONTROL OF FLUORIDATION OF PUBLIC WATER SUPPLY IN ANÁPOLIS, GOIÁS. (CIPEEX, 2025)
The addition of fluoride to water is one of the most effective methods for preventing dental caries at the population level. For water fluoridation to be effective in controlling and preventing caries, it is important that fluoride be maintained at adequate concentrations, which should range from 0.55 to 0.84 mg/L in daily water consumption. The following study aims to verify and map water distribution by observing the difference in fluoride concentration at selected collection points near and far from water treatment plants (ETAs) to inspect whether fluoride levels are being consistently maintained in the city of Anápolis.
Keywords: Fluoride; Water fluoridation; Public health; Control; Prevention